On automaticity as a constituent of virtue - Peters, Julia (Ethical theory and moral practice, 2015)
A large part of the current debate among virtue ethicists focuses on the role played by phronesis, or wise practical reasoning, in virtuous action. The paradigmatic case of an action expressing phronesis is one where an agent explicitly reflects and deliberates on all practical options in a given situation and eventually makes a wise choice. Habitual actions, by contrast, are typically performed automatically, that is, in the absence of preceding deliberation. Thus they would seem to fall outside of the primary focus of the current virtue ethical debate. By contrast, Bill Pollard has recently suggested that all properly virtuous actions must be performed habitually and therefore automatically, i.e. in the absence of (a certain kind of) moral deliberation. In this paper, Pollard's suggestion is interpreted as the thesis that habitual automaticity is constitutive of virtue or moral excellence. By constructing an argument in favor of it and discussing several objections, the paper ultimately seeks to defend a qualified version of this thesis.
Gesehen am 30.11.2022